Complex Fourier transform of currents or voltages of 3-phase system based on Clarke and extended Fortescue transform - Wojciechowski, D. (Scientific Journal of Gdynia Maritime University, 2017)
Fourier transform is a fundamental method of signal decomposition, includingtransients of currents and voltages. Spectra of 3-phase quantities are usual independent forall the phases. The drawback of this method is that it doesn’t explicitly show the kind ofasymmetry of particular harmonics. Asymmetry is usually defined in practice with Fortescuetransform, regarding only fundamental harmonics, thus asymmetry of remaining harmonicsis neglected. The paper presents two methods of frequency representation of 3-phasesystem quantities, which provides complete and explicit information both about harmonicdistortion and asymmetry. The methods utilize, respectively, Clarke, and Fortescuetransformations. There is also shown the equivalency of both methods.